Female Imam and Khatib: The Shifting in Worship Traditions from Progressive to Conservative in Sungai Landia, West Sumatra, Indonesia - Busyro Busyro; Arsal Arsal; Maizul Imran; Mohd Nasran Mohamad; Edi Rosman; Saiful Amin (Institut Agama Islam Negeri Batusangkar, 2023)
The changes in the implementation of eid prayers in Sungai Landia by abolishing women’s rights to become imam and khatib do not necessarily eliminate the progressive sides of Sungai Landia women. This study aims at exploring the persistence of progressive sides in the transition process of eid prayer tradition from female imam and khatib to conservative fiqh provisions. This research is qualitative in nature with the main data obtained from community leaders and women from Sungai Landia. The data analysis was carried out using a descriptive method. This study concludes that the process of changing to conservative fiqh was carried out by going through the stages of fiqh scientific deepening and socialization for four years to avoid chaos in society. The community began to realize their mistake because of criticism from various parties. The criticisms were not only from the local community, but also from the ulama who were invited to give religious lectures. Sungai Landia women accepted the change with the condition that male and female congregations must still be separate in implementing eid prayers even though the imam and khatb are men. There are progressive sides that are still maintained by paying attention to aspects of gender equality and social justice to create peace in worship as evidenced by the existence of public recognition for women to be separate from men in carrying out the eid prayers.